Enhancing Science Education in Primary Teacher Training: An Analysis of Course Implementation and Pedagogical Practices - Diana Ayu Rostikawati; Riandi Riandi; Diana Rochintaniawati; Wahyu Sopandi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Improving the quality of science education in teacher training is essential for developing competent educators. This study focuses on enhancing science instruction within the Primary School Teacher Education program at a private university in Serang City, Banten, by examining the implementation of the science course and related pedagogical practices. A descriptive qualitative approach was employed, involving five sixth-semester pre-service teachers as participants. Data were collected through structured interviews lasting 30–45 minutes. The interviews explored multiple facets of the course, including syllabus availability, lesson plan alignment, instructional media usage, access to teaching materials, application of instructional models, learning activity sheets, assessment practices, and course activities. Findings indicate inconsistencies between course plans and classroom activities. Participants reported limited access to teaching resources and inconsistent use of instructional media. However, they emphasized the value of interactive activities and the need for varied assessment tools. Feedback highlighted the importance of structured syllabi, engaging media, and creative approaches that align with different learning styles. The results underscore the importance of student input in improving science education courses. Enhancements should focus on providing comprehensive instructional materials, integrating technology, and promoting pedagogical creativity. Diverse teaching strategies and assessment methods can foster active engagement and support the professional growth of pre-service teachers. Structured, student-informed improvements in course design and delivery are essential to prepare effective future educators, especially in science education.